Hubungan Beban Kerja Fisik dan Shift Kerja dengan Kelelahan Kerja Pada Karyawan Operator Packing di PT So Good Food-Unit UHT Boyolali - Sumardiyono; Mutiara Putri Pertiwi; Dian Nugroho (Journal of Applied Agriculture, Health, and Technology, 2023)
Work fatigue is still a major occupational safety and health issue for packing operators at PT. So Good Food-Unit UHT Boyolali. This is in line with data showing that 32.8% of 58,115 workers in Indonesia suffer from work fatigue. In 2021, there were 262 occupational accidents in Central Java, of which 50% were caused by work fatigue. This study aimed to analyze the relationship between physical workload and shift work with work fatigue. This study is an observational analytic study with a cross-sectional design. The respondents were taken from 55 packing operator employees of PT. So Good Food-Unit UHT Boyolali from a total of 121 employees. The sampling technique used was Disproportionate Stratified Random Sampling. This study used a finger pulse oximeter to measure the level of physical workload and a reaction timer to measure the level of work fatigue, while shift work data was obtained through the company's shift work schedule. Data analysis techniques used were the Somers’d Test and the Multiple Ordinal Logistic Regression Test. The results of the Somers’d Test showed that there was a relationship between physical workload and work fatigue (d = 0.783; p = 0.001), and there was a relationship between shift work and work fatigue (d = 0.783; p = 0.001). The results of a multiple ordinal logistic regression test proved that shift work was the most influential variable on work fatigue with an OR = 7.205. There was a significant relationship between physical workload and shift work with work fatigue in packing operator employees at PT. So Good Food-Unit UHT Boyolali.